УРОВЕНЬ ЛИПОКАЛИНА В КРОВИ И МОЧЕ У БОЛЬНЫХ ОСТРЫМ КОРОНАРНЫМ СИНДРОМОМ В ЗАВИСИМОСТИ ОТ СТРАТЕГИИ РЕВАСКУЛЯРИЗАЦИИ - М. А. Шаленкова; З. Д. Михайлова; П. Ф. Климкин (Архивъ внутренней медицины)
S-NGAL and u-NGAL content was examined for 113 acute coronary syndrome (ACS) patients, depending on revascularization strategy. 39 (66,1%) ACS patients had transcutaneous coronary treatment (TCT), 41 myocardial infarction (MI) patients with ST segment rise (MI-STR) had thrombolytic therapy (TLT). Higher s-NGAL and u-NGAL levels were obtained for patients with haemodynamically meaningful stenoses (HMS) of coronary arteries (CA) as compared with patients not having HMS. S-NGAL and u-NGAL content for MI-STR patients was higher for patients receiving non-effective, rather than effective TLT, and for patients with contraindications to TLT. Both s-NGAL and u-NGAL levels were higher for MI-STR patients to whom farmacoinvasive strategy was applied, as compared to using only one revascularization method.